Microbiology - Cornelissen, Cynthia Nau (Lippincott's illustrated reviews., 2013)
"Lippincott's Illustrated Reviews: Microbiology, Third Edition enables rapid review and assimilation of large amounts of complex information about medical microbiology. The book has the hallmark features for which Lippincott's Illustrated Reviews volumes are so popular: an outline format, 450 full-color illustrations, end-of-chapter summaries, review questions, plus an entire section of clinical case studies with full-color illustrations. NEW TO THIS EDITION: an online testbank of 100 review questions"--Provided by publisher.